Sustainable Development of Green Supply Chain: A Case Study on Alibaba - Feng, Xiaoyu (Transactions on Economics, Business and Management Research, 2024)
The ongoing advancement of global economic integration and the flourishing growth of e-commerce have led to the swift rise of the logistics business. This expansion has concurrently resulted in a range of environmental problems. The heightened utilization of packing materials and the energy expenditure associated with transportation have exerted pressure on the environment. This paper examines Alibaba’s green packaging project, focusing on its initiatives in ecologically friendly packaging materials, packaging recycling and reuse, and supply chain optimization. This paper comprehensively examines the beneficial impacts, current issues, and obstacles associated with the execution of Alibaba’s green packaging project. This analysis explores the significant influence of supply chain technical innovation, the utilization of environmentally friendly materials, and the integration of green energy with low-carbon transportation on the sustainable development of the supply chain. Moreover, many recommendations are proposed for Alibaba, such as advancing green technological innovation and implementation, fortifying green supply chain management, and augmenting consumers’ understanding and engagement in sustainability initiatives.